Effects of rarity form on species’ responses to land use - Louise Sykes; Luca Santini; Adrienne Etard; Tim Newbold (Conservation Biology, 2020)
Anthropogenic land‐use change causes substantial changes in local and global biodiversity. Rare and common species can differ in sensitivity to land‐use change; rare species are expected to be affected more negatively. Rarity may be defined in terms of geographic range size, population density, or breadth of habitat requirements. How these 3 forms of rarity interact in determining global responses to land use is yet to be assessed. Using global data representing 912 vertebrate species, we tested for differences in responses to land use of species characterized by different types of rarity. Land‐use responses were fitted using generalized linear mixed‐effects models, allowing responses to vary among groups of species with different forms of rarity. Species considered rare with respect to all 3 forms of rarity showed particularly strong declines in disturbed land uses (>40% of species and 30% of individuals in the most disturbed land uses). In contrast, species common both geographically and numerically and with broad habitat requirements showed strong increases (up to 90% increase in species and 40% in abundance in some land uses). Our results suggest that efforts to understand the vulnerability of species to environmental changes should account for different types of rarity where possible. Our results also have potentially important implications for ecosystem functioning, given that rare species may play unique roles within ecosystems.